Evidence to Support Controversy in Microsurgery. Issue 3 (March 2015) - Fan, Kenneth L.; Patel, Ketan M.; Mardini, Samir; Attinger, Christopher; Levin, L. Scott; Evans, Karen K.
Abstract : Summary: Microsurgery practice, including preoperative patient selection, intraoperative technique, and anesthetic considerations, varies from institution to institution and from surgeon to surgeon. Many surgeons' practices are driven by "conventional wisdom, " which is handed down from mentors to fellows and residents. In this article, the authors explore the oxymoron that there is evidence to support controversy in microsurgery. Indeed, if there was convincing evidence to support varying microsurgery practices, there would be no controversy. The authors conducted a review with a focus on evidence-based medicine to support microsurgery practice.